Предмет: Алгебра,
автор: PUKACHU228
Упростите пожалуйста
Приложения:
![](https://files.topotvet.com/i/146/146617ee903cee5ec5a0cfafc0ea8968.jpg)
Ответы
Автор ответа:
0
4-3у/у+4÷ ( (4-у) (у-4)+у (у+4)/(у+4)(у-4) )=4-3у/у+4×(у+4)(у-4)/-у^2-16+у^2+4у=(4-3у)(у-4)/-16+4у=(4-3у) (у-4)/4(у-4)=4-3у/4
Похожие вопросы
Предмет: Геометрия,
автор: instabilityplease
Предмет: Математика,
автор: otomchik091
Предмет: Математика,
автор: bekjankanybekov247
Предмет: Математика,
автор: MARVEL20161983
Предмет: Математика,
автор: Катя1200хорошистка